2018
DOI: 10.1016/j.canlet.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Nimbolide reduces CD44 positive cell population and induces mitochondrial apoptosis in pancreatic cancer cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is highly aggressive disease and current treatment regimens fail to effectively cure PDAC. Development of resistance to current therapy is one of the key reasons for this outcome. Nimbolide (NL), a triterpenoid obtained from Azadirachta indica, exhibits anticancer properties in various cancer including PDAC cells. However, the underlying mechanism of this anticancer agent in PDAC cells remains undefined. We show that NL exerts a higher level of apoptotic cell death compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Consistent with our results, Kumar et al reported that CD44 was overexpressed and contributed to poor 5-year OS rate in pancreatic cancer patients. 21 Furthermore, CD44 expression was notably high and associated with dismal clinical outcomes in cancers including non-small-cell lung cancer, 22 breast cancer, 16 oral squamous cell carcinoma, 23 ovarian cancer 24 and gastric cancer. 25 All these findings suggested that CD44 could be a biomarker for early diagnosis or prognosis prediction of GBC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Kumar et al reported that CD44 was overexpressed and contributed to poor 5-year OS rate in pancreatic cancer patients. 21 Furthermore, CD44 expression was notably high and associated with dismal clinical outcomes in cancers including non-small-cell lung cancer, 22 breast cancer, 16 oral squamous cell carcinoma, 23 ovarian cancer 24 and gastric cancer. 25 All these findings suggested that CD44 could be a biomarker for early diagnosis or prognosis prediction of GBC.…”
Section: Discussionmentioning
confidence: 99%
“…An overwhelming body of evidence indicates that nimbolide inhibits the proliferation of cancer cells by inducing apoptosis 11 13 , 19 26 . Nimbolide has been reported to transduce apoptosis by modulating signalling networks that regulate both the intrinsic and extrinsic pathways of apoptotic cell death 13 , 15 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The GO and KEGG enrichment analyses suggest that these DEmRNAs have a significant effect on tumor-associated biological functions. Among the 12 total pathways, 'focal adhesion', 'ECM-receptor interaction', 'microRNAs in cancer' and 'proteoglycans in cancer' are associated with the progression of PDAC (45)(46)(47)(48). The PPI network was established, including the six hubgenes (THBS1, FN1, TGFB2, ITGA1, ITGA3, and TIMP3), to further identify the key circRNAs participating in the regulatory network.…”
Section: Discussionmentioning
confidence: 99%